Kegiatan Preservasi dan Konservasi Koleksi Kantor Pos Besar Kota Medan pasca Alih Fungsi ke Pos Bloc - Elisa Ananda Br. Hutapea; Yusra Dewi Siregar (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
Preservation and conservation as an effort to preserve collections at the Medan City Post Office after the function has been switched to be public space called 'Pos Bloc'. The purpose of this study is to determine the process of preservation and conservation activities and the factors causing damage to collectibles at the Pos Bloc. This research is qualitative descriptive. The process of data analysis uses the theory of Miles and Huberman, namely by reducing the data focusing on the research theme, presenting explaining data based on observations, interviews, and documentation, and concluding the results of the analysis after the stages of analysis are completed. While testing the validity of data in this study was carried out in four ways, namely: credibility, transferability, dependability, and confirmability. In this study, the informants were staff officers as many as two informants. The results of this study show that the Pos Bloc has various factors from damage to collectibles, ranging from environmental factors, namely lack of air humidity, biological factors, namely termite insects, physical factors, namely dust, and human factors, namely ignorance of hands. The strategy of the Medan City Post Office in preserving collectibles is to make improvements. The actions taken by the Medan City Post Office in preserving collectibles are damage prevention measures such as gathering visitors and cleaning rooms, as well as repairing collectibles.